2021
DOI: 10.17508/cjfst.2021.13.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of thin layer drying characteristics of blanch-assisted water yam (Dioscorea alata) slices

Abstract: The thin layer drying characteristics of blanch-assisted water yam slices were investigated with respect to its un-blanched water yam slices in a convective hot air oven. The yam slices (diameter 4 cm; thickness 0.8 cm) were dried at temperatures 50, 60 and 70 °C, respectively with a constant air velocity of 0.13 m/s. The drying data obtained were fitted into six existing drying models: Page, Newton, Midilli, Henderson and Pabis, Logarithmic and Diffusion model. Non-linear regression analysis was used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…Therefore, the complete drying process for all apple varieties occurred within the range of the falling rate period. Similar results were obtained in drying studies carried out on various agricultural products such as peas Kucuk 2017), strawberries (El--Beltagy et al 2007), peaches (Kingsly et al 2009), and yam (Okeleye et al 2021).…”
Section: Resultssupporting
confidence: 77%
“…Therefore, the complete drying process for all apple varieties occurred within the range of the falling rate period. Similar results were obtained in drying studies carried out on various agricultural products such as peas Kucuk 2017), strawberries (El--Beltagy et al 2007), peaches (Kingsly et al 2009), and yam (Okeleye et al 2021).…”
Section: Resultssupporting
confidence: 77%
“…Based on the computed activation energy from the straight line slope (14.93 kJ/mol), 1 mol of water in the WFSP requires 14.93 kJ of energy to dry. This result was remarkably similar to the water yam's (Okeleye et al, 2021). Selvi (2020) reported that most agricultural products have E a values ranging from 14.42 to 43.26 kJ/mol due to various drying procedures.…”
Section: E F F E a And Specific Energy Consumptionsupporting
confidence: 82%